FORMULATION AND EVALUATION OF TRANSDERMAL PATCH OF CARICA PAPAYA - Linku A; Manvini S
Pharmacological studies have shown that Carica papaya possessed anti-inflammatory, antioxidant and wound healing properties. The present study was outlined to extract, formulate and evaluate C. papaya transdermal patches. Transdermal patches were made by solvent casting method utilizing HPMC as rate controlling polymer and glycerine as plasticizer. Polysorbate 80 was used as penetration enhancer. It was assessed for various characteristics, such as thickness, surface pH, folding endurance, weight variation, % moisture uptake, % moisture loss and stability studies. The prepared patches showed good folding endurance, hence low chances of patch to break. The thickness, surface pH, weight variation values gave satisfactory results. The % moisture uptake and moisture loss indicated good stability of film. From all evaluation parameters, formulation F2 was finalized as optimized patch. The prepared patches showed satisfactory results.